Microblog: An Interactive Learning Media for Learning English - Sri Dwi Nurbayti; Muhammad Candra; Rona Elfiza (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
This research intended to design a Microblog on Instagram as interactive learning media to learn the descriptive text for Grade 7. The media designed to assist students comprehend in English learning, especially descriptive text. This research was conducted at SMP Negeri 16 Tanjungpinang for the academic year 2021/2022 on class VII E, which consisted of 38 students. This research was Research and Development (R&D). The development model was Thiagarajan model which are 4D (Define, Design, Develop, and Disseminate). Moreover, this research was limited to Develop stage. The instrument to collect the data was several questionnaires which consist of validation questionnaire and student practicality questionnaire. The results of data analysis revealed that the score of media validation is 86% with